ANALYSIS OF PRODUCTIVITY BASED ON KPI CASE STUDY AUTOMOTIVE PAINT INDUSTRY - Paduloh Paduloh (Badan Penerbit Jurnal, Faculty of Engineering, Universitas Brawijaya, 2020)
The research was aimed to measure and analyze productivity in production department at Paint Industry for Automotive, the criteria used are Quantity of production, number of sales, stock of raw materials, bad stock, electricity usage, loss production, machine breakdown, overtime hours, product stock productivity and Productivity of washing solvent usage. Data was obtained based on questionnaires and company data, the analysis was carried out using Objective Matrix Method and Company Key Performance Indicator to determine the level of company productivity. The results showed that the productivity of the company was low and unstable. Production productivity was the highest productivity but this productivity was not in accordance with the productivity conditions of other companies such as sales, raw material usage, labor, electricity usage, machine breakdown, and bad stock. Another highly contradictory productivity is the amount of overtime production numbers are not following the increase in the quantity of production. When production productivity rose, the productivity of other supporters decreased. These contradictory conditions indicate that the productivity of the quantity of production can still continue to be improved with make stronger controls for other support activities in line production.